A case report on glomus caroticum tumors and preoperative embolisation - Ahmet Koç; Ahmet Mert Bilgili; Orhan Altıntaş; Turgay Han (Turkish Archives of Otorhinolaryngology, 2004)

(untitled)
Glomus tumors (chemodectomas) originate from chemoreceptors in the neural crest. Two thirds of glomus tumors in head and neck region are glomus jugulare tumors. Tumors originating from carotid bifurcation are called glomus caroticum. They are slowly growing tumors. Methods for management are follow- up with MR-scan, radiotherapy and surgical excision. Preoperative intravascular embolisation provides an easy surgical excision of glomus caroticum tumors. In this case report, glomus caroticum tumors and preoperative embolisation have been discussed.